An Unusual Spectrum of Anaphylactoid Reaction to Vancomycin During General Anesthesia - Zahid Hussain Khan (Archives of Anesthesia and Critical Care, 2015)
This case report describes an unusual spectrum of a proved anaphylactoid reaction to vancomycin during general anesthesia for release of tethered spinal cord in a 14 year old girl. Bronchospasm which is the sine qua non of a classical anaphylactoid reaction was singularly absent in this particular case. Our objective in this presentation is to highlight the importance of early recognition of this potentially fatal drug reaction which should be taken into consideration in the absence of bronchospasm if other clinical signs are subtle and unequivocal.